Systemic exposure of oxaliplatin and docetaxel in gastric cancer patients with peritonitis carcinomatosis treated with intraperitoneal hyperthermic chemotherapy. Issue 2 (February 2021) - Koemans, W.J.; van der Kaaij, R.T.; Wassenaar, E.C.E.; Grootscholten, C.; Boot, H.; Boerma, D.; Los, M.; Imhof, O.; Schellens, J.H.M.; Rosing, H.; Huitema, A.D.R.; van Sandick, J.W.
Abstract: In the PERISCOPE I study, gastric cancer patients with limited peritoneal dissemination were treated with systemic chemotherapy followed by (sub)total gastrectomy, cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC) with 460 mg/m 2 hyperthermic oxaliplatin followed by normothermic docetaxel in escalating doses (0, 50, 75 mg/m 2 ). In total, 25 patients completed the study protocol. Plasma samples were collected before the start of the HIPEC procedure, after oxaliplatin washing, after docetaxel washing and the following morning. Median peak plasma concentrations were 5.5∗10 −3  mg/ml for oxaliplatin, 89∗10 −6  mg/ml for docetaxel (dose 50 mg/m 2 ) and 113∗10 −6  mg/ml for docetacel (dose 75 mg/m2). The following morning median plasma concentrations were 32% and 4% of the measured peak concentrations for oxaliplatin and docetaxel, respectively. For both cytostatic agents, no correlation was found between intraperitoneal fluid concentration and peak plasma concentration. High doses oxaliplatin and docetaxel can be given intraperitoneally without causing potentially toxic systemic concentrations.